Comparative Numerical Analysis between Two Types of Orthodontic Wire for the Lingual Technique, Using the Finite Element Method - Rosa Alicia Hernández-Vázquez; Rodrigo Arturo Marquet-Rivera; Octavio Alejandro Mastache-Miranda; Angel Javier Vázquez-López; Salvador Cruz-López; Juan Alejandro Vázquez-Feijoo (Applied Bionics and Biomechanics)
In the lingual orthodontic technique, there are two paradigms regarding the type of wire used. Regardless of the material or gauge, some orthodontists choose to use the straight wire and resin and bond it to the surface of the tooth; they call it compensations. Other orthodontists prefer to bend the wire, giving it a mushroom shape. There is no specific indication for the use of each type of wire, so orthodontists use them according to their criteria. The present study establishes the bases so that it is possible to find the indications for each type of wire. A clinical trial of a lingual orthodontic patient was used. To carry out the comparative study, a straight arch was placed in his right arch and a mushroom arch in the left arch. Using 3D imaging, a high-biofidelity biomodel of the patient’s mandible was generated, with which the FEM analysis was performed, which allowed comparing the reactions of the mandibular bone and appliances with the different arches. It was found that, on the side with the straight arch, there were greater deformations, and in the mushroom arch, there were greater stresses. With this, it is possible to find which clinical cases in each type of wire are indicated.